2014
DOI: 10.1063/1.4859855
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical simulation of electrostatic striped colloidal particles

Abstract: The static and dynamic properties of striped colloidal particles are obtained using molecular dynamics computer simulations. Striped particles with n = 2 to n = 7 stripes of alternating electric charge are modeled at a high level of detail through a pointwise (PW) representation of the particle surface. We also consider the extent to which striped particles are similar to comparable isotropically attractive particles-such as depletion attracting colloids-by modeling striped particles with an isotropic pair int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The combination of hard core and soft interactions (including Coulomb forces) are used in more elaborated models like the CHARMM and AMBER force fields, the DLVO potential for spherically symmetrical colloidal particles or colloids with asymmetrically distributed surface charges …”
Section: Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of hard core and soft interactions (including Coulomb forces) are used in more elaborated models like the CHARMM and AMBER force fields, the DLVO potential for spherically symmetrical colloidal particles or colloids with asymmetrically distributed surface charges …”
Section: Potentialsmentioning
confidence: 99%
“…The combination of hard core and soft interactions (including Coulomb forces) are used in more elaborated models like the CHARMM 29,30 and AMBER 31,32 force fields, the DLVO potential for spherically symmetrical colloidal particles 33 or colloids with asymmetrically distributed surface charges. [34][35][36] In some cases, the pairwise additivity assumption breaks down. Typical corrections involve the minimal inclusion of 3-body and higher-order-body forces successively in the potential as needed to obtain agreement with experiment.…”
Section: Model Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A selected snapshot of Hernandez’s research efforts shown (clockwise from top left) through journal covers spanning across transition state theory (reprinted with permission from ref , copyright 2010 Elsevier), Janus and striped particles (reprinted with permission from ref , copyright 2014 AIP Publishing), diffusion through complex environments (reprinted with permission from ref , copyright 2010 American Chemical Society), stochastic hard collisions (reprinted with permission from ref , copyright 2018 Elsevier), sustainable nanoparticles (reprinted with permission from ref , copyright 2016 American Chemical Society), and diversity equity (reprinted with permission from ref , copyright 2018 American Chemical Society).…”
Section: Introductionmentioning
confidence: 99%
“…The phase and spatial behavior observed in the assembly of a monomeric species into oligomeric clusters drives the design of materials with unique functionalities. At atomistic length scales, the structural complexity arising from assembly is often difficult to describe using analytical theory or to simulate on relevant time scales due to the large numbers of degrees of freedom that constitute such systems. To reduce this complexity, the atomistic degrees of freedom can be reduced to a coarse-grained (CG) description where a group of atomic degrees of freedom is mapped onto a single CG site. At mesoscopic length scales, CG macromolecules can be modeled using repulsive potentials that are finite valued at the origin, i.e., bounded potentials. , The finite nature of bounded interactions allows for multiple macromolecules to overlap and occupy the same volume in configuration space. , Studies of mesoscopic systems with interactions dictated by bounded potentials include colloid suspensions, polymer–colloid mixtures, star polymers, and block copolymers. , …”
Section: Introductionmentioning
confidence: 99%